Effects of Vibration Therapy on Hormone Response and Stress in Severely Disabled Patients: A Double‐Blind Randomized Placebo‐Controlled Clinical Trial. Issue 3 (6th August 2013) - Seco, J.; Rodríguez‐Pérez, V.; López‐Rodríguez, A. F.; Torres‐Unda, J.; Echevarria, E.; Díez‐Alegre, M. I.; Ortega, A.; Morán, P.; Mendoza‐Laíz, N.; Abecia Inchaurregui, L. C.
Abstract Purpose To assess the effects of vibration therapy (VT) on quality of life and hormone response in severely disabled patients compared with placebo. Design A longitudinal prospective, double‐blind, randomized placebo‐controlled trial, with pre and postintervention assessments. Methods A total of 20 severely disabled individuals were recruited from a National Reference Centre in Spain: 13 (65%) men and 7 (35%) women, 45.5 ± 9.32 years of age (range 41: 22–63). We evaluated their physical stress and state anxiety. Results No statistically significant changes were found in the socio‐psychological variables studied, while in the experimental group state anxiety decreased significantly with p < 0.01 (Z = 2.38; one‐tailed p = .009) and, among the biological variables, the level of cortisol fell (p = 0.03). Conclusion Short periods of exposure to low‐frequency and low‐amplitude local vibration are a safe and effective mechanical stimulus that can have a positive effect in terms of hormone response. Clinical Relevance: VT can be considered to have an anti‐stress effect.